EXPERIMENTAL STUDY OF SELF-SUFFICIENT PILOT-SCALE PYROLYSIS ON INSTANT NOODLE PLASTIC PACKAGING - Bong, Nicolaus
The rapid economic and population growth are two factors of the increasing waste generation. Based on the conducted Municipal Solid Waste (MSW) composition survey, 15.7% of MSW contained plastic waste, in which 4.6% were Non Recycled Plastic (NRP). These NRP wastes accumulate in landfills due to the lack of proper waste management. NRP waste problem arises, due to its low value, making them unpopular material to be recycled. Pyrolysis process was proposed in this research. Pyrolysis converts NRP waste into liquid fuel with high calorific value. However, the energy sufficiency of the pyrolysis process to treat NRP waste was still unknown. A 100 L pilot-scale batch reactor was used to pyrolyze instant noodle plastic packaging samples as a representative of NRP waste. Sample of 4.7 kg were pyrolyzed using kerosene burner as the heating source in three processing temperatures of 400 ?, 450 ?, and 500 ?, producing two distinctive pyrolytic oils and condensed into two different temperatures. The heating values, oil yields, and fuel consumptions were then used to define the recommended operating temperature. The recommended temperature was found to be 500 ? as it had the highest net energy produced from the process of 35.2 MJ. The heating values of the pyrolytic oils from the first outlet and second outlet were found to be 46.86 MJ/kg and 45.86 MJ/kg, densities of 789.3 kg/m3 and 761.1 kg/m3, and kinematic viscosities of 3.66 cSt and 1.51 cSt, respectively. The obtained pyrolytic oils were then used as kerosene substitute for the subsequent pyrolysis process. The result showed that applying the pyrolytic oil sped up the process by 13.0%, and gained higher net energy than that of kerosene. The system’s energy self-sufficiency was attainable as the net energy produced totaled to 48.1 MJ. In the end, simple economic feasibility was conducted using sensitivity analysis. It was revealed that the worker’s payroll had the largest effect on cashflow. In order to achieve breakeven point, worker’s payroll needs to be reduced by 84%, or increase the oil selling price to 382%, or increase the sales volume to 504%. It can be concluded that the developed pyrolysis process could be sustainable in the aspect of energy but still uneconomical.